Wiring dendrites in layers and columns. (2nd April 2016) - Luo, Jiangnan; McQueen, Philip G.; Shi, Bo; Lee, Chi-Hon; Ting, Chun-Yuan
Abstract: The most striking structure in the nervous system is the complex yet stereotyped morphology of the neuronal dendritic tree. Dendritic morphologies and the connections they make govern information flow and integration in the brain. The fundamental mechanisms that regulate dendritic outgrowth and branching are subjects of extensive study. In this review, we summarize recent advances in the molecular and cellular mechanisms for routing dendrites in layers and columns, prevalent organizational structures in the brain. We highlight how dendritic patterning influences the formation of synaptic circuits.